PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LIKUIDITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Nurul Faiseh; Ghina Fitri Ariesta Susilo (Melati Institute, 2022)
Issuance of going concern opinion that influences inventor’s decisions, makes going concern opinion matter that must receive attention for the company. This study aims to provide empirical evidence regarding the effect of company size, profitability, and liquidity on the acceptance of going concern opinions in companies. Manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2019-2020 are the objects selected in the research. As for the sample selection in this study using purposive sampling with logistic regression data analysis. From the research conducted, it can be found that the size of the company has no effect on the acceptance of going concern audit opinions, while profitability and liquidity have an influence on the acceptance of going concern opinions.